Implementasi Augmented Reality untuk Karya Isometrik pada Animation Art Exhibition (Animaxtion) - Tito Ari Pratama; Ely Rosita (Universitas Multimedia Nusantara, 2023)
In exhibitions, animated artwork also develops following technological advances and the needs of exhibition visitors. One of the concepts of the exhibition is to exhibit isometric drawings as shown in the exhibition, then visualize them in 3D animation using the Augmented Reality method. Augmented Reality is a technology that runs and combines digital content created by computers in real-time. In the results of the research that has been carried out, if the results of the implementation of Augmented Reality (AR) using Unity software have been successfully implemented on Android-based Smartphones and Tablets by practicing Isometric objects that are displayed when smartphones with the Android operating system or Tablet trigger prints of student work which contain printed images of work in Animaxtion. Keywords: augmented reality; unity; animaxtion; isometric.